Adolescents' value formation in the superhero fandom - Santos, Joseph Russell R. (Animo Repository, 2019)
The Superhero Fandom is a fan group that continues to grow across the globe because of the notable characters and stories found in comic books, television series, and films. To determine what fans specifically attain from this community, the present study aimed to explore the value formation of adolescents in the superhero fandom. Fifteen adolescents from the Philippines were individually interviewed to gather the data needed. In addition, two local online superhero fan communities were observed for a week. Thematic analysis of the interviews show that adolescent fans adopt values such as helpfulness, doing what is right, concern for the well-being of others, optimism, and perseverance. Furthermore, the findings also reveal that adolescent fans get these values from viewing superhero-related fan material, witnessing a character’s ability and experiences, participating in fan discussions and social media, and playing superhero video games. Relatedly, these values and the fandom itself are helpful in their personal lives in that they have something to relate to, a source of happiness and satisfaction, the chance to address the challenges of life, and a feeling of a sense of belongingness. On the other hand, the results from the observed online fan communities do not show any relevant data that answer the research questions because probing the members was not part of the objective for the present study. Nevertheless, the same online groups have been found to be a venue for the free sharing of information about the fandom. Overall, the findings suggest that the superhero fandom is a context for the formation of values that are essential in positive youth development.